2019
DOI: 10.1016/j.carbon.2018.10.085
|View full text |Cite
|
Sign up to set email alerts
|

Gateless and reversible Carrier density tunability in epitaxial graphene devices functionalized with chromium tricarbonyl

Abstract: Monolayer epitaxial graphene (EG) has been shown to have clearly superior properties for the development of quantized Hall resistance (QHR) standards. One major difficulty with QHR devices based on EG is that their electrical properties drift slowly over time if the device is stored in air due to adsorption of atmospheric molecular dopants. The crucial parameter for device stability is the charge carrier density, which helps determine the magnetic flux density required for precise QHR measurements. This work p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…6 However, the reduction of the electron density from the order of 10 13 cm −2 to the order of 10 10 cm −2 by the presence of Cr(CO) 3 considerably assists the p region to undergo its transition. 16 It should be briefly noted that the temporary dip in resistivity near t = 30000 s arises from another competing process to shift the carrier density, namely that of the applied heat, which as prescribed by other work, causes n-type doping in EG devices. 16 Transport measurements were performed at 4 K, allowing us to determine the lowtemperature longitudinal resistivity (ρ xx ), mobility (μ), and electron density in EG (n G ), where the latter two parameters are calculated by the following respective formulas:…”
Section: Assessing the Quality Of The Charge Configurations And Pnjsmentioning
confidence: 89%
See 2 more Smart Citations
“…6 However, the reduction of the electron density from the order of 10 13 cm −2 to the order of 10 10 cm −2 by the presence of Cr(CO) 3 considerably assists the p region to undergo its transition. 16 It should be briefly noted that the temporary dip in resistivity near t = 30000 s arises from another competing process to shift the carrier density, namely that of the applied heat, which as prescribed by other work, causes n-type doping in EG devices. 16 Transport measurements were performed at 4 K, allowing us to determine the lowtemperature longitudinal resistivity (ρ xx ), mobility (μ), and electron density in EG (n G ), where the latter two parameters are calculated by the following respective formulas:…”
Section: Assessing the Quality Of The Charge Configurations And Pnjsmentioning
confidence: 89%
“…[1][2][3][4] Epitaxial graphene (EG) on silicon carbide (SiC), which can be grown on the centimeter scale and is one of the many methods of synthesizing graphene, exhibits properties that render it suitable for large-scale or high-current applications such as the continued development of quantized Hall resistance (QHR) standards. [5][6][7][8][9][10][11][12][13][14][15] Though modernday standards using millimeter-scale EG have been shown to have long-term electrical stability in ambient conditions, 16 these devices are, in most cases, only able to output a single value of quantized resistance (ν = 2 plateau) to a degree of accuracy which warrants possible use in metrology. The corresponding value is: One milestone for graphene QHR standards would be the eventual accessibility of different resistance values that are well-quantized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wet-etching procedure removes the Pd/Au in the defined areas without harming the EG. The finished devices are functionalized with chromium tricarbonyl [Cr(CO) 3 ], which provides tunable and uniform doping without the need for large-scale electrostatic gates [12].…”
Section: Device Preparation and Characterizationmentioning
confidence: 99%
“…Additionally, a variety of ligands can be used to stabilize the electronic properties of the -conjugated carbon surfaces as recently reported in a study of the ( 6 -graphene)Cr(CO)3 complex, which has been suggested as an exceptionally robust quantum Hall resistance standard. 50 with the grid localization used in the code, optimizes the efficiency of the calculation so that most of the time-consuming computations scale linearly with time. We utilized the dispersion-corrected PBE-TS exchange correlation functional 52,53 in all of our calculations since van der Waals interactions play a significant role in SWNT junctions, and further details on the PBE-TS approach for carbon nanostructures are described further in ref.…”
Section: ( ) ( )mentioning
confidence: 99%